ABILITY VO2MAX FRESHMAN STUDIES PJKR STKIP PASUNDAN CIMAHI 2016/2017 ACADEMIC YEAR - Friskawati, Gita Febria (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2016)
The purpose of this study was to determine VO2max kemamapuan freshman PJKR study program STKIP Pasundan Cimahi Academic Year 2016/2017. The population in this study were all new students study program PJKR STKIP Pasundan Cimahi Academic Year 2016/2017 which amounted to 432 people. Sampling technique used in this study is Purpousive Sampling, sample in this study as many as 40 new student study program PJKR STKIP Pasundan Cimahi Academic Year 2016/2017. The instrument used to measure the level of VO2max is a test Beep Test with the criteria of Davis, at.all (1992). The method used is descriptive quantitative method. Data from the description shows that the level of VO2max for student daughter has a category Superior 7%, 7% in the category of Very Good, 8% in the Good category, 10% in the Medium category, 25% in less category and 43% in the category Very Less. Overall it can be concluded that the ability to VO2 Max on a new student study program PJKR STKIP Pasundan Cimahi 2016/2017 Academic Year in the category of very less. Based on the research results, it is necessary efforts to improve the ability of VO2 Max on a new student study program through lectures PJKR kecabangan practice sports.